Subclinical tuberculosis linkage to care and completion of treatment following community-based screening in rural South Africa - Zolelwa Sifumba; Helgard Claassen; Stephen Olivier; Palwasha Khan; Hloniphile Ngubane; Thokozani Bhengu; Thando Zulu; Mareca Sithole; Dickman Gareta; Vukuzazi Team; Mahomed-Yunus S. Moosa; Willem A. Hanekom; et al. (BMC, 2024)
Abstract Background Tuberculosis (TB), a leading cause of infectious death, is curable when patients complete a course of multi-drug treatment. Because entry into the TB treatment cascade usually relies on symptomatic individuals seeking care, little is known about linkage to care and completion of treatment in people with subclinical TB identified through community-based screening. Methods Participants of the Vukuzazi study, a community-based survey that provided TB screening in the rural uMkhanyakude district of KwaZulu-Natal from May 2018 - March 2020, who had a positive sputum (GeneXpert or Mtb culture, microbiologically-confirmed TB) or a chest x-ray consistent with active TB (radiologically-suggested TB) were referred to the public health system. Telephonic follow-up surveys were conducted from May 2021 - January 2023 to assess linkage to care and treatment status. Linked electronic TB register data was accessed. We analyzed the effect of baseline HIV and symptom status (by WHO 4-symptom screen) on the TB treatment cascade. Results Seventy percent (122/174) of people with microbiologically-confirmed TB completed the telephonic survey. In this group, 84% (103/122) were asymptomatic and 46% (56/122) were people living with HIV (PLWH). By self-report, 98% (119/122) attended a healthcare facility after screening, 94% (115/122) started TB treatment and 93% (113/122) completed treatment. Analysis of electronic TB register data confirmed that 67% (116/174) of eligible individuals started TB treatment. Neither symptom status nor HIV status affected linkage to care. Among people with radiologically-suggested TB, 48% (153/318) completed the telephonic survey, of which 80% (122/153) were asymptomatic and 52% (79/153) were PLWH. By self-report, 75% (114/153) attended a healthcare facility after screening, 16% (24/153) started TB treatment and 14% (22/153) completed treatment. Nine percent (28/318) of eligible individuals had TB register data confirming that they started treatment. Conclusions Despite high rates of subclinical TB, most people diagnosed with microbiologically-confirmed TB after community-based screening were willing to link to care and complete TB treatment. Lower rates of linkage to care in people with radiologically-suggested TB highlight the importance of streamlined care pathways for this group. Clearer guidelines for the management of people who screen positive during community-based TB screening are needed.